Imaging of Endolymphatic and Perilymphatic Fluid at 3T After Intratympanic Administration of Gadolinium-Diethylene-Triamine Pentaacetic Acid - Naganawa, S.; Sugiura, M.; Kawamura, M.; Fukatsu, H.; Sone, M.; Nakashima, T. (American Journal of Neuroradiology, 2008)
SUMMARY: By optimizing the inversion time of a 3D inversion-recovery turbo spin-echo sequence at 3T, we obtained separate images of endolymphatic and perilymphatic space 24 hours after intratympanic administration of gadolinium contrast material. In patients with Ménière disease, endolymphatic hydrops were detected not only in the cochlea but also in the vestibule. Fusion of the 2 types of images visualized the entire fluid space of the labyrinth and the spatial relationship of the 2 spaces.